MATERIALS FOR THE STUDY OF PALEOSOLS OF THE PALASA-SYRT MOUNDS (GROUP №7) - Idrisov, I A (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers the results of the research of buried soils of mound group No. 7 of the southern section of the Palasa-Syrt burial mound of the 4th-5th centuries, conducted in 2016. The findings complement the data of the previous studies (2009-2015). The explored buried soils may be grouped according to various peculiarities of natural environment and anthropogenic development of the territory.